Static and dynamic characteristics of jumping skis - Gim, J.; Joen, J.; Kim, B.; Jeong, T.; Rhee, B. (Science and Skiing VII, 2018)
Physical characteristics of skis affect the ski-jumping performance, important ski characteristics are largely determined by the geometry and material properties. To understand how skis behave, the physical properties—such as bending and torsional stiffness and damping characteristics—should be figured out (Lind & Sanders, 2013). In the four stages of ski jumping, the effects of static and dynamic characteristics appear differently. Stiffness distribution and vibration characteristics influence the pressure and fluctuation of the pressure distribution in the in-run and take-off stages. In the flight stage, vibration of skis affects flight stability and controllability (Hildebrand, Drenk & Müller, 2009; Sasaki et al., 2012). In the landing stage, the afterbody stiffness may influence landing stability. Therefore, static and dynamic characteristics of jumping skis have various relationships with not only take-off but also the other stages.